2022
DOI: 10.1111/jopy.12777
|View full text |Cite
|
Sign up to set email alerts
|

Broad and narrow environmental and genetic sources of personality differences: An extended twin family study

Abstract: ObjectiveSeveral personality theories distinguish between rather genetically rooted, universal dispositional traits (DTs) and rather environmentally shaped, more contextualized characteristic adaptations (CAs). However, no study so far has compared different measures of theoretically postulated DTs and CAs regarding their environmental and genetic components while considering differences in measurement abstraction and reliability. This study aims to bridge this gap by testing the assumed differences in the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
(102 reference statements)
2
6
0
Order By: Relevance
“…Emotional stability was the only characteristic to provide specific additive genetic variance and also showed the comparably largest amount of these effects in general. These findings accord with existing theories viewing emotional stability as a broader and more basic tendency or dispositional trait and, in contrast, self-esteem or control beliefs as characteristic adaptations (McAdams & Pals, 2006; McCrae & Costa, 2008), since dispositional trait differences were frequently expected to yield comparably larger heritability estimates (Kandler et al, 2014; Kandler & Rauthmann, 2022; Kandler et al, in press). Our results on unique additive genetic variance in emotional stability correspond to these assumptions and amplify that emotional stability might be specifically distinguishable from the other three self-evaluative characteristics with respect to a broader scope.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Emotional stability was the only characteristic to provide specific additive genetic variance and also showed the comparably largest amount of these effects in general. These findings accord with existing theories viewing emotional stability as a broader and more basic tendency or dispositional trait and, in contrast, self-esteem or control beliefs as characteristic adaptations (McAdams & Pals, 2006; McCrae & Costa, 2008), since dispositional trait differences were frequently expected to yield comparably larger heritability estimates (Kandler et al, 2014; Kandler & Rauthmann, 2022; Kandler et al, in press). Our results on unique additive genetic variance in emotional stability correspond to these assumptions and amplify that emotional stability might be specifically distinguishable from the other three self-evaluative characteristics with respect to a broader scope.…”
Section: Discussionsupporting
confidence: 89%
“…1.The present twin data has been used in another study (Kandler et al, in press), but with regard to a very different research question not referring to the structure and sources of common variance underlying the four self-evaluative characteristics.…”
mentioning
confidence: 99%
“…This multinational effort to understand values in the Mediterranean region (including seven countries from three continents) is an impressive illustration in furthering our understanding of the role of cultural fit for well-being in young adults. Kandler et al (2023; this issue) provided a comprehensive analysis of the genetic and environmental components of a host of psychological characteristics that are theorized to have different levels of environmental sensitivity (i.e., dispositional traits [Big Five and HEXACO traits and facets] and characteristic adaptations [goals, interests, moral concerns, values, religiosity, self-esteem, control, selfefficacy, and well-being]). Using extended twin family and spouses-of-twins models, they confirmed that the variance in dispositional traits can be attributable to genetic influences and that variance in characteristics adaptations can be attributable to environmental influences.…”
Section: Overview Of Papersmentioning
confidence: 99%
“…This special issue highlights that the call to go beyond traits is still relevant. However, we want to point to the few articles in our special issue that went beyond traits (e.g., Atherton et al, 2023; Du et al, 2023; Kandler et al, 2023; Kirchner‐Häusler et al, 2023). These included personality constructs such as values, well‐being, goals, interests, religiousness, and self‐schemas.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…However, heritability estimates include gene-environment interplay processes which could lead to high heritability estimates with many modi able environmental risk factors, or novel interventions could be designed to work in tandem with genetically in uenced characteristics (e.g., wearing eyeglasses). We favor the approach taken byKandler et al (2022) which uses behavior genetic estimates as one data point among many to guide inferences. In this context, agency appears to re ect an intermediate variable.…”
mentioning
confidence: 99%